1999
DOI: 10.1074/jbc.274.42.29683
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Distinction of Phosphatidylcholine Synthesis between the CDP-Choline Pathway and Phosphatidylethanolamine Methylation Pathway

Abstract: In addition to the CDP-choline pathway for phosphatidylcholine (PC) synthesis, the liver has a unique phosphatidylethanolamine (PE) methyltransferase activity for PC synthesis via three methylations of the ethanolamine moiety of PE. Previous studies indicate that the two pathways are functionally different and not interchangeable even though PC is the common product of both pathways. This study was designed to test the hypothesis that these two pathways produce different profiles of PC species. The PC species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
271
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(288 citation statements)
references
References 26 publications
5
271
1
3
Order By: Relevance
“…The Lipid Content of the Liver Is Altered in CT␣ Knockout Mice-The Kennedy (CDP-choline) pathway has been shown to produce ϳ70% of PC in the liver (7,9). It was, therefore, expected that deletion of CT␣ would alter hepatic lipid concentrations.…”
Section: Identification Of the Liver-specific Ct␣ Knockout Mice-mentioning
confidence: 99%
See 1 more Smart Citation
“…The Lipid Content of the Liver Is Altered in CT␣ Knockout Mice-The Kennedy (CDP-choline) pathway has been shown to produce ϳ70% of PC in the liver (7,9). It was, therefore, expected that deletion of CT␣ would alter hepatic lipid concentrations.…”
Section: Identification Of the Liver-specific Ct␣ Knockout Mice-mentioning
confidence: 99%
“…Liver cells are unique in that they can also synthesize PC via the sequential methylation of phosphatidylethanolamine catalyzed by phosphatidylethanolamine N-methyltransferase (PEMT) (6). The PEMT pathway accounts for ϳ30% of hepatic PC biosynthesis, whereas the enzymes of the Kennedy pathway produce the remaining 70% (7)(8)(9).…”
mentioning
confidence: 99%
“…The inability of PEMT to rescue MT58 cells under restrictive temperature from apoptosis suggests that the PC species generated from the Kennedy pathway and the PEMT pathway are functionally different (Cui and Houweling, 2002). Indeed, the PC species derived from PE methylation contain longer and more unsaturated fatty acid chains than the PC species generated through the Kennedy pathway (DeLong et al, 1999). The only PC capable of rescuing MT58 cells at the nonpermissive temperature from apoptosis is PC generated through the Kennedy pathway (Esko et al, 1982;Ostrander et al, 2001).…”
Section: Mechanism Of Action Of Choline Kinase Inhibitorsmentioning
confidence: 99%
“…The only PC capable of rescuing MT58 cells at the nonpermissive temperature from apoptosis is PC generated through the Kennedy pathway (Esko et al, 1982;Ostrander et al, 2001). Changes in the nature of PC in membranes may cause alterations in the fluidity, structural integration and association of membrane proteins, vesicular traffic, affinity and activity of lipases (DeLong et al, 1999).…”
Section: Mechanism Of Action Of Choline Kinase Inhibitorsmentioning
confidence: 99%
“…Recent studies investigating the proportion of hepatic PC that is derived from each pathway defined the PEMT-controlled pathway as the source of 30% of hepatic PC with the CDP-choline pathway accounting for 70% (7)(8)(9). Significantly perhaps, data from one group also revealed that the PEMT pathway is a metabolically channeled process suggesting that PEMT-derived PC may be destined for a specific function (9).…”
mentioning
confidence: 99%